'Our family picture is a little hint of heaven': race, religion and selective reproduction in US 'embryo adoption'. (November 2020) - Cromer, Risa
Abstract: People use selective reproductive technologies (SRT) in various family-making practices to assist with decisions about which children should be born. The practice of 'embryo adoption', a form of embryo donation developed by white American evangelical Christians in the late 1990s, is a novel site for reconceptualizing SRT and examining how they function among users. Based on ethnographic research conducted between 2008 and 2018 on US 'embryo adoption', this study provides an anthropological analysis of media produced by and about one white evangelical couple's race-specific preferences for embryos from donors of colour. This article shows how racializing processes and religious beliefs function as mutually reinforcing SRT for some 'embryo adoption' participants. Evangelical convictions justify racialized preferences, and racializing processes within and beyond the church reinforce religious acts. Race-specific preferences for embryos among white evangelicals promote selective decision-making not for particular kinds of children, a current focus in studies of SRT, but for particular kinds of families. This study expands the framework of SRT to include selection for wanted family forms and technologies beyond biomedical techniques, such as social technologies like racial constructs and religious convictions. Broadly, this article encourages greater attention to religion within analyses about race and reproduction by revealing how they are deeply entwined with Christianity, especially in the USA. Wherever constructions of race and religious convictions co-exist with selective reptroductive decision-making, scholars should consider race, reproduction and religion as inextricable, rather than distinct, domains of analysis.